We start with the equation \(4^{2x-5} = 2^{3x+7}\). Since \(4\) can be expressed as \(2^2\), we rewrite the left side of the equation:
\[
(2^2)^{2x-5} = 2^{3x+7}
\]
Step 2: Simplify the Exponents
Using the property of exponents \((a^m)^n = a^{m \cdot n}\), we simplify the left side:
\[
2^{4x - 10} = 2^{3x + 7}
\]
Step 3: Set the Exponents Equal
Since the bases are the same, we can set the exponents equal to each other:
\[
4x - 10 = 3x + 7
\]
Step 4: Solve for \(x\)
To isolate \(x\), we rearrange the equation:
\[
4x - 3x = 7 + 10
\]
This simplifies to:
\[
x = 17
\]